The Distribution of Wages in Belarus - Alina Verashchagina; Francesco Pastore (Institute for the Study of Labor (IZA), 2004)
This paper uncovers evidence on the distribution of wages in Belarus in the second half of the 1990s. The returns to education and work experience are high and stable, which is atypical for a transition country. This might be due to the pervasive role of the state in fixing wages in the dominant budget sector, rather than to market forces coming into play. Women experience contained, though largely unexplained discrimination coupled with higher than average returns to education. A wage curve effect is found, which is similar in size to that of other transition countries, but much higher than in market economies.
Keywords: D31; P2; J31; 330; wage distribution; returns to education; gender wage gap; wage curve; Belarus; Lohnstruktur; Bildungsertrag; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Regionale Lohnstruktur; Regionale Arbeitslosigkeit; Schätzung; Weissrussland